The role of the inferior frontal gyri in cognitive processing of patients with Parkinson's disease: a pilot rTMS study - Srovnalova, Hana; Marecek, Radek; Rektorova, Irena (Movement disorders, 2011)
BACKGROUND: We studied whether 1 session of high-frequency repetitive transcranial magnetic stimulation (rTMS) applied sequentially over both the left and right inferior frontal gyri (IFG) would enhance performance in tests evaluating the ability to inhibit habitual responses (Stroop test, ST; Frontal Assessment Battery, FAB) in patients with Parkinson's disease (PD). METHODS: Ten nondemented PD patients (6 men, 4 women; age, 66 ± 6 years; disease duration, 5.4 ± 2.45 years) entered the randomized, sham stimulation-controlled study with a crossover design. The ST and the FAB were performed prior to and immediately after an appropriate rTMS session. RESULTS: The active but not sham rTMS induced significant improvement in all ST subtests (word, color, color-word). Conversely, the calculated Stroop interference and the FAB scores remained unchanged. CONCLUSIONS: In PD patients, rTMS of the IFG increased the speed of cognitive processing in both the congruent and incongruent conditions of the ST.
Keywords: Female; klinické křížové studie; čelní lalok; Parkinsonova nemoc; Neuropsychological Tests; kognitivní poruchy; Color Perception; ženské pohlaví; vnímání barev; neuropsychologické testy; lidé; transkraniální magnetická stimulace; dvojitá slepá metoda; Pilot Projects; Mental Status Schedule; pilotní projekty; Cross-Over Studies; Cognition Disorders; Frontal Lobe; Humans; Double-Blind Method; Male; Aged; inhibice (psychologie); záznam o duševním stavu; Transcranial Magnetic Stimulation; lidé středního věku; senioři; mužské pohlaví; Inhibition, Psychological; Middle Aged; Vocabulary; Parkinson Disease; slovní zásoba